Babyface effects: A double‐edged sword in healthcare service evaluations. Issue 4 (15th June 2015) - Chang, Chun‐Tuan; Chen, Cheng‐Xuan
<x xml:space="preserve">Abstract</x> We examine how a doctor's baby‐like facial appearance affects people's perceptions and judgments before and after a medical fraud occurs. A 2 (face type: babyfaced vs maturefaced) × 2 (doctor's gender: male vs female) × 2 (doctor's specialty: internal medicine vs surgery) between‐subjects experiment was conducted. The results indicate that a babyfaced doctor fares better than a maturefaced doctor in terms of patients' expectations, satisfaction and intended loyalty. However, having baby‐like facial features may work against a doctor who is involved in a medical fraud. The severity of a medical fraud is perceived to be greater when it involves either a babyfaced female doctor of internal medicine or a babyfaced male surgeon. After the medical fraud, this altered perception of the fraud's severity leads to reduced patient loyalty. Service evaluations based on the doctor‐patient relationship show that the doctor's baby face is a double‐edged sword.